Dimension Synthesis of a Spatial Parallel Kinematic Manipulator Based on S-shaped Test Specimen - Liu Yuzhe; Wu Jun; Wang Liping; Wang Jinsong (MATEC Web of Conferences, 2017)
With the development of the aerospace industry, the hybrid machine tool for machining the complicated curved surface is becoming a research hotspot. The S-shaped test specimen proposed by Chengdu Aircraft Industrial Company is an effective test method to verify the ability of machining the complicated curved surface for a machine tool. Considering the spatial parallel kinematic manipulator in a hybrid machine tool provides the complicated orientation motion and its design of structure dimension affects the accuracy of the machine tool, this paper investigates the issue about dimension synthesis of the manipulator based on S-shaped test specimen. By establishing models of the S-shaped test specimen and parallel kinematic manipulator, the motion trajectory of the parallel kinematic manipulator for machining S-shaped test specimen is obtained. According to the motion trajectory and expected performance indices, the result of dimension synthesis for the manipulator is plotted and a set of suitable dimensions is achieved. With the analysis result in this paper, it is helpful to improving the accuracy of machining the S-shaped test specimen.